The Effect of Psychoreligy Dzikir Intervention on Self Efficacy and Blood Pressure on Hypertension - Adivtian Ragayasa; Sylvina Rahmawati; Emdat Suprayitno (Universitas STRADA Indonesia, 2022)
Background: Hypertension is a chronic disease condition that causes impaired self-efficacy and increased blood pressure. One of the non-pharmacological therapies that can do is dzikir or dhikr therapy. Purpose: This study aimed to determine the effect of remembrance therapy on self-efficacy and blood pressure in hypertension. The study was an experimental study using a Randomized Pre Test-Post Test Control Group Design in hypertensive patients receiving psycho religious therapy. The subjects in this study were all hypertensive patients in the working area of ??the Teja Pamekasan Health Center, as many as 20 people. Methods: The selected sample in this study was some hypertensive patients taken by simple random sampling. Blood pressure measurements were carried out twice before psycho religious therapy and two weeks after psycho religious therapy. Psychoreligious therapy is a series of dhikr and prayer by saying the letter